Evil in modern thought : an alternative history of philosophy - Neiman, Susan (UK Princeton university press, 2002)
"Evil threatens human reason, for it challenges our hope that the world makes sense. For eighteenth-century Europeans, the Lisbon earthquake was manifest evil. Today we view evil as a matter of human cruelty, and Auschwitz as its extreme incarnation. Examining our understanding of evil from the Inquisition to contemporary terrorism, Susan Neiman explores who we have become in the three centuries that separate us from the early Enlightenment. In the process, she rewrites the history of modern thought and points philosophy back to the questions that originally animated it."--Jacket
FIRE FROM HEAVEN -- God's Advocates: Leibniz and Pope -- Newton of the Mind: Jean-Jacques Rousseau -- Divided Wisdom: Immanuel Kant -- Real and Rational: Hegel and Marx -- In Conclusion -- CONDEMNING THE ARCHITECT -- Raw Material: Bayle's Dictionary -- Voltaire's Destinies -- The Impotence of Reason: David Hume -- End of the Tunnel: The Marquis de Sade -- Schopenhauer: The World as Tribunal -- ENDS OF AN ILLUSION -- Eternal Choices: Nietzsche on Redemption -- On Consolation: Freud vs. Providence -- HOMELESS -- Earthquakes: Why Lisbon? -- Mass Murders: Why Auschwitz? -- Losses: Ending Modern Theodicies -- Intentions: Meaning and Malice -- Terror: After September 11 -- Remains: Camus, Arendt, Critical Theory, Rawls -- Origins: Sufficient Reason
Includes bibliographical references (p. [337]-343) and index
Keywords: Good and evil -- History; Philosophy, Modern; History